Differential effects of Th1, monocyte/macrophage and Th2 cytokine mixtures on early gene expression for molecules associated with metabolism, signaling and regulation in central nervous system mixed glial cell cultures - Lisak, Robert P (BioMed Central, 2009)
BACKGROUND: Cytokines secreted by immune cells and activated glia play central roles in both the pathogenesis of and protection from damage to the central nervous system (CNS) in multiple sclerosis (MS). METHODS: We have used gene array analysis to identify the initial direct effects of cytokines on CNS glia by comparing changes in early gene expression in CNS glial cultures treated for 6 hours with cytokines typical of those secreted by Th1 and Th2 lymphocytes and monocyte/macrophages (M/M). RESULTS: In two previous papers, we summarized effects of these cytokines on immune-related molecules, and on neural and glial related proteins, including neurotrophins, growth factors and structural proteins. In this paper, we present the effects of the cytokines on molecules involved in metabolism, signaling and regulatory mechanisms in CNS glia. Many of the changes in gene expression were similar to those seen in ischemic preconditioning and in early inflammatory lesions in experimental autoimmune encephalomyelitis (EAE), related to ion homeostasis, mitochondrial function, neurotransmission, vitamin D metabolism and a variety of transcription factors and signaling pathways. Among the most prominent changes, all three cytokine mixtures markedly downregulated the dopamine D3 receptor, while Th1 and Th2 cytokines downregulated neuropeptide Y receptor 5. An unexpected finding was the large number of changes related to lipid metabolism, including several suggesting a switch from diacylglycerol to phosphatidyl inositol mediated signaling pathways. Using QRT-PCR we validated the results for regulation of genes for iNOS, arginase and P glycoprotein/multi-drug resistance protein 1 (MDR1) seen at 6 hours with microarray. CONCLUSION: Each of the three cytokine mixtures differentially regulated gene expression related to metabolism and signaling that may play roles in the pathogenesis of MS, most notably with regard to mitochondrial function and neurotransmitter signaling in glia.